2019
DOI: 10.3102/0002831219842347
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Implementation of Formative Assessment in Three Large Urban Districts

Abstract: In this study, we examined the enactment of formative assessment by administrator-selected master teachers in large, urban, public school districts in three regions of the United States. Furthermore, this study also included an investigation of the perceptions and frequency of use for all teachers within the same districts to gather a snapshot of the state of use of formative assessment within those settings overall. Currently, the research base is limited regarding how effective teachers implement formative a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 32 publications
3
19
0
1
Order By: Relevance
“…However, the high prevalence of teacher-centric assessors builds on previous research that has suggested teachers in the U.S. use formative assessment primarily to guide their teaching (e.g., diagnostic quizzes, questioning; Barnes et al, 2017;Erickson, 2007). The observed teacher-centric approaches in the U.S. thus support findings that formative assessment strategies that build student agency and metacognition (e.g., self-assessment) are areas not widely realized in the U.S. context (Johnson et al, 2019). Our findings reflect the prevalence of a specific formative perspective on assessment in the U.S. that focuses on standardized diagnostic assessment rather than involving students actively in assessment processes (Bloom et al, 1971).…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…However, the high prevalence of teacher-centric assessors builds on previous research that has suggested teachers in the U.S. use formative assessment primarily to guide their teaching (e.g., diagnostic quizzes, questioning; Barnes et al, 2017;Erickson, 2007). The observed teacher-centric approaches in the U.S. thus support findings that formative assessment strategies that build student agency and metacognition (e.g., self-assessment) are areas not widely realized in the U.S. context (Johnson et al, 2019). Our findings reflect the prevalence of a specific formative perspective on assessment in the U.S. that focuses on standardized diagnostic assessment rather than involving students actively in assessment processes (Bloom et al, 1971).…”
Section: Discussionsupporting
confidence: 62%
“…Interviews with hesitant and moderately student-centric assessors could also illuminate why teachers hold these two approaches. Additionally, given that our findings support research that suggests teachers in the U.S. make limited use of student-centered formative assessment approaches (e.g., self-and peer assessment; Johnson et al, 2019), extensions of our study would interrogate the barriers that limit such practices. The suggested future directions would inform ways to support teachers in applying contemporary standards.…”
Section: Future Directionssupporting
confidence: 61%
See 1 more Smart Citation
“…This is the case found in Young and Jackman ( 2014) study. Johnson, Sondergeld, and Walton (2019) discovered the same especially when it comes to certain FA strategies. Alkharusi, Kazem, and Al-Musawai (2011) and Yamtim and Wongwanich (2014) explained that this is due to teachers' belief that they are incompetent.…”
Section: Introductionmentioning
confidence: 73%
“…However, there are strategies such as differentiated learning, addressing learning gap, effective feedback and peer-and self-assessment which were not practised enough by the respondents. These strategies have been identified as difficult and may be one of the reasons behind the lack of use of FA (Johnson et al, 2019;Lysaght & O'Leary, 2013;Pastore et al, 2019). This difficulty causes teachers to view FA as an added burden instead of seeing it as one of important elements in their teaching (Coffey, Hammer, Levin, & Grant, 2011).…”
Section: Discussionmentioning
confidence: 99%